Leading With Principle: The Essential Role of Ethical Leadership in Adaptive Environments - Askew, Nanci P. (Journal of Leadership, Accountability and Ethics, 2023)
In the fluid landscape of modern business, adaptability emerges as a crucial element for organizational success. This article delves into the dynamics of adaptable work environments, emphasizing the critical role of ethical leadership in navigating the transition from flexible to toxic work cultures. Drawing on insights from thought leaders like Arena, Heffernan, and Brown, and anchored by a case study of a start-up’s evolution, the discussion illuminates how ethical leadership forms the backbone of adaptable organizations. The paper highlights the dangers of a toxic workplace and the transformative power of diversity and mentorship. It underscores the necessity of maintaining a balance between adaptability and a strong ethical foundation, illustrating the interplay between organizational flexibility, ethical leadership, and long-term success. This comprehensive analysis serves as a guide for leaders striving to foster sustainable adaptability, grounded in ethical principles, ensuring organizations not only thrive but also uphold their moral core in an ever-evolving business world.